2016
DOI: 10.1111/jopr.12450
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Universal Cementation Technique for Implant‐Supported Crowns with Subgingival Margins

Abstract: Restoration of implant crowns with subgingival margins has always been a challenge. If done precisely it leads to better treatment outcomes and prognosis. An incorrect technique and improper execution of the luting procedure are known to cause a high incidence of peri-implant disease due to incomplete elimination of the luting agent. Deep subgingival abutment margins are difficult to recognize, and cement removal in these cases becomes complicated if the sulcus depth is greater than 3 mm. Irrespective of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This value was determined from earlier studies that found a cement spacer of approximately 50 μm resulted in improved seating accuracy of cast restorations (Campagni, Wright & Martinoff, ; Wilson, , ; Wu & Wilson, ). Using the pre‐cementation techniques with individualized implant abutments require elaborate custom‐made devices prepared by the dental technician or fabricated chair side (Bhushan et al., ; Chee et al., ; Rayyan & Makarem, ; Wadhwani & Pineyro, ). Any material residue from the custom analog has to be removed from the inner crown surface, particularly when adhesive cementation techniques are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value was determined from earlier studies that found a cement spacer of approximately 50 μm resulted in improved seating accuracy of cast restorations (Campagni, Wright & Martinoff, ; Wilson, , ; Wu & Wilson, ). Using the pre‐cementation techniques with individualized implant abutments require elaborate custom‐made devices prepared by the dental technician or fabricated chair side (Bhushan et al., ; Chee et al., ; Rayyan & Makarem, ; Wadhwani & Pineyro, ). Any material residue from the custom analog has to be removed from the inner crown surface, particularly when adhesive cementation techniques are used.…”
Section: Discussionmentioning
confidence: 99%
“…A cementation technique was introduced in 2002 in which a pre‐cementation device (e.g., abutments or abutment analogs) is fitted into the cement‐filled crown to displace excess cement and provide a uniform thin cement layer before the final crown seating (Dumbrigue, Abanomi & Cheng, ). This technique has been further developed by making a so‐called practice or copy abutment from vinyl polysiloxane putty (Chee, Duncan, Afshar & Moshaverinia, ; Wadhwani & Pineyro, ), hot thermoplastics (Rayyan & Makarem, ), or bis‐acrylic temporary restorative material (Bhushan, Aras, Chitre, Mysore & Daswani, ) in chair‐side fabrication. A PTFE tape was also used to facilitate a cement space of 50 μm and to avoid surface contamination from the vinyl polysiloxane putty used in making the analog (Wadhwani & Pineyro, ).…”
Section: Introductionmentioning
confidence: 99%
“…Current recommendations suggest clinicians to place cementation margins subgingivally in order to hide the abutment–crown interface. , However, deeper position margins have been associated with a higher risk for undetected residual cement, and cement remnants can only be successfully removed when the margin is placed supragingivally. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several techniques have been suggested for controlling or minimising submucosal residual cement around implant‐retained restorations. These include the use of polytetrafluoroethylene (Teflon) tape (Hess, 2014), rubber dams (Seo & Seo, 2017), gingival displacement cord or copy abutment (Bhushan et al., 2017; Canullo et al., 2016; Caudry et al., 2009; Galván et al., 2015; Lee et al., 2016; Liang et al., 2016; Rayyan & Makarem, 2016; Wadhwani & Piñeyro, 2009; Yuzbasioglu, 2014), and others. According to the literature, a rubber dam allows only a minimal amount of excess cement to flow into the submucosal area even when the prosthesis margins are submucosally placed.…”
Section: Introductionmentioning
confidence: 99%